PENGARUH KUALITAS PRODUK, INFLUENCER MARKETING, DAN BRAND IMAGE TERHADAP MINAT BELI ULANG PADA PRODUK KOSMETIK Y.O.U. DI KOTA DENPASAR - Putu Devita Pradnyasari; I Gusti Ayu Imbayani; I Made Surya Prayoga (VALUES, 2024)
To determine a marketing strategy, you need to understand repurchase interest. By understanding repurchase interest, companies can know consumer needs and consumer desires. The interest in repurchasing is the result of resolutely solving the problems they face. This research aims to examine the influence of product quality, influencer marketing and brand image on interest in repurchasing Y.O.U cosmetic products in Denpasar City. This research was conducted in Denpasar City among consumers of Y.O.U cosmetic products with a sample of 75 respondents in this study. The sample determination method in this study was taken using the Hair formula. Data collection was carried out through documentation, interviews and questionnaire methods. The data analysis technique used in this research is multiple linear regression analysis using the SPSS version 26 program. Based on the results of the analysis, this research shows that product quality has a positive and significant effect on repurchase interest in Y.O.U Cosmetics products in Denpasar City. This means that the better the quality of Y.O.U Cosmetics products in Denpasar City, the better the interest in repurchasing. Influencer marketing has a positive and significant effect on interest in repurchasing Y.O.U Cosmetics products in Denpasar City. This means that the better the influencer marketing for Y.O.U Cosmetics products in Denpasar City, the better the interest in repurchasing. Brand image has a positive and significant effect on repurchase interest in Y.O.U Cosmetics products in Denpasar City. This means that the better the brand image of Y.O.U Cosmetic Products in Denpasar City, the better the interest in repurchasing.